Diet Quality and Cancer Outcomes in Adults: A Systematic Review of Epidemiological Studies - Potter, Jennifer (Int J Mol Sci, 2016)
Dietary patterns influence cancer risk. However, systematic reviews have not evaluated relationships between a priori defined diet quality scores and adult cancer risk and mortality. The aims of this systematic review are to (1) describe diet quality scores used in cohort or cross-sectional research examining cancer outcomes; and (2) describe associations between diet quality scores and cancer risk and mortality. The protocol was registered in Prospero, and a systematic search using six electronic databases was conducted through to December 2014. Records were assessed for inclusion by two independent reviewers, and quality was evaluated using a validated tool. Sixty-four studies met inclusion criteria from which 55 different diet quality scores were identified. Of the 35 studies investigating diet quality and cancer risk, 60% (n = 21) found a positive relationship. Results suggest no relationship between diet quality scores and overall cancer risk. Inverse associations were found for diet quality scores and risk of postmenopausal breast, colorectal, head, and neck cancer. No consistent relationships between diet quality scores and cancer mortality were found. Diet quality appears to be related to site-specific adult cancer risk. The relationship with cancer mortality is less conclusive, suggesting additional factors impact overall cancer survival. Development of a cancer-specific diet quality score for application in prospective epidemiology and in public health is warranted.